Just another tablet? Identifying barriers to statin uptake in patients living with HIV - Adam Darnley; Aarzoo Bhatia; Evelyn Ikekpeazu; Chitra Babu; Anna Garner; Orla McQuillan; Andrew Tomkins; Chris Ward; Clare Wood (Clinical Medicine, 2025)
Introduction: People living with HIV (PLHIV) are at increased risk of cardiovascular disease. The Randomized Trial to Prevent Vascular Events in HIV (REPRIEVE) demonstrated benefits of statin therapy for this population.1 In response, the British HIV Association (BHIVA) issued guidance recommending statin therapy for PLHIV ≥40 years old.2 This study aimed to assess the proportion of patients recommended a statin during clinic visits, whether these recommendations translate into prescriptions in primary care, and the barriers to statin uptake. Materials and Methods: A random sample of PLHIV aged ≥40 years who attended an HIV appointment since March 2024 was selected. Data were collected from electronic patient records, including cardiovascular risk factors, QRISK3 scores and previous statin use. Statin prescribing was assessed by reviewing current medications at the next clinic visit or in GP records as of 31 December 2024. Patients were excluded from prescribing analysis if statin advice was within 4 weeks of data collection or if GP records were unavailable. Patients recommended a statin in clinic but not taking one at follow-up were invited to complete a questionnaire via telephone or in clinic. The questionnaire explored the information received about statins, reasons for non-initiation, concerns about statin use and potential strategies to improve uptake. Results and Discussion: 271 cases were reviewed, 26% were women and the mean age was 53 years (range 40–84). Lifestyle advice was documented for 192 (70.8%). Of the 203 patients not already on statins, 111 (54.7%) were recommended a statin in clinic. Patients with a QRISK3 score >5% were more likely to be recommended a statin (χ²(1)=37.85, p<0.001), in accordance with BHIVA’s suggestion for prioritisation.2 However, 70% of patients with a QRISK3 score <5% were not offered a statin. Age was significantly associated with statin recommendation (regression coefficient=0.01, p=0.001, R²=0.05) 28 patients declined the statin recommendation in clinic. Among those who did not decline, 73.6% had not been prescribed a statin at follow-up. Of the 24 patients who completed the questionnaire, 22 (91.7%) recalled receiving advice about statins in clinic, but only 11 (45.8%) recalled being informed about both the benefits and risks. Nine patients wanted to start a statin but were unable to obtain a GP appointment. Eight patients raised concern about tablet burden, seven were concerned about side effects and five received negative information from family, friends or online sources (Fig 1). Participants suggested that ‘more transparent discussions around side effects’ and more personalised cardiovascular risk information could improve decision-making. Conclusion: This study highlights the disparity between statin recommendations and prescriptions in PLHIV. More focus is needed on recommending statins to lower-risk patients in clinic. For those offered a statin, clinicians must consider the burden of polypharmacy and potential side effects, underscoring the need for more balanced discussions. Structural barriers, particularly delays in GP appointments, further hinder uptake. A multifaceted approach is needed: enhanced patient counselling with individualised discussions, patient information leaflets to support informed decision-making, and stronger coordination with primary care, including educational sessions for GPs.